genesis - Beevis, Christine (UnderCurrents: Journal of Critical Environmental Studies, 1999)
thoughts, armed with daggers wage battles behind my eyes -- soldiers riding memories -- multi-coloured horses pave hooves into the valleys of my mind [...]